2006
DOI: 10.1152/ajpendo.00246.2006
|View full text |Cite
|
Sign up to set email alerts
|

No effect of menstrual cycle phase on basal very-low-density lipoprotein triglyceride and apolipoprotein B-100 kinetics

Abstract: (TG), increased total and LDL-cholesterol concentrations and decreased HDL-cholesterol concentration, is an important risk factor for cardiovascular disease. Premenopausal women have a less atherogenic plasma lipid profile and a lower risk of cardiovascular disease than men, but this female advantage disappears after menopause. This suggests that female sex steroids affect lipoprotein metabolism. The impact of variations in the availability of ovarian hormones during the menstrual cycle on lipoprotein metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 63 publications
(65 reference statements)
3
34
0
Order By: Relevance
“…This is very similar to the error estimates for VLDL-apoB-100 FTR and all other outcome variables in the present study in men. In addition, the day-to-day variability reported here in men is no less than the intraindividual variability for basal FFA, VLDL-TG, and VLDL-apoB-100 kinetics that we recently reported when studying premenopausal women once during the follicular phase and once during the luteal phase of the menstrual cycle (11). This finding strengthens our conclusion from the previous study that menstrual cycle Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is very similar to the error estimates for VLDL-apoB-100 FTR and all other outcome variables in the present study in men. In addition, the day-to-day variability reported here in men is no less than the intraindividual variability for basal FFA, VLDL-TG, and VLDL-apoB-100 kinetics that we recently reported when studying premenopausal women once during the follicular phase and once during the luteal phase of the menstrual cycle (11). This finding strengthens our conclusion from the previous study that menstrual cycle Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1) (7, 13, 28, 30). The total rate of VLDL-TG secretion (mmol/min), which represents the total amount of VLDL-TG secreted by the liver, was calculated by multiplying the FTR of VLDL-TG (pools/min) by the concentration of VLDL-TG in plasma (mmol/l) and the plasma volume (liters) (10,11,13); plasma volume was assumed to equal the VLDL-TG volume of distribution and was calculated as 0.055 l/kg fat-free mass (31). VLDL-TG plasma clearance rate (ml plasma/min) was calculated by dividing the VLDL-TG secretion rate by VLDL-TG concentration in plasma (i.e., FTR 3 plasma volume).…”
Section: Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sex differences in the plasma lipid profile have traditionally been attributed to differences in the sex hormone milieu; particularly the availability of estradiol, but also progesterone. However, we and others have shown that changes in ovarian steroid concentration during the normal menstrual cycle (26) and after menopause (6,23,50) are not associated with changes in very-low-density lipoprotein (VLDL)-TG and VLDL-apolipoprotein B-100 (apoB-100) kinetics and concentrations that are consistent with the observed sexual dimorphism in VLDL metabolism (53). Furthermore, oral estrogen preparations given to women and men increase total plasma TG and VLDL-TG concentrations due to increased hepatic VLDL-TG secretion, and transdermal administration of 17␤-estradiol, which better mimics normal endogenous estrogen delivery, does not affect or only modestly decreases (by Ͻ10%) plasma TG concentration (53).…”
mentioning
confidence: 66%